1965
DOI: 10.1136/jcp.18.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical demonstration of gamma glutamyl transpeptidase activity in bone marrow and blood cells

Abstract: SYNOPSIS The demonstration by a histochemical method of gamma glutamyl transpeptidase is described. In marrow and peripheral blood it has been found useful in differentiating between normal and leukaemic myeloblasts and between marrow (short-lived) lymphocytes and lymph node (long-lived) lymphocytes. The method may also be of value in differentiating between normal and neoplastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1966
1966
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…It is also present in various body fluids, such as saliva, serum, bile and urine (Nemesanzky and Lott, 1985;Sener, 1997). GGT has been detected both in blood and bone marrow cells by using cytochemical methods (Szmigielski et al, 1965). It has been demonstrated at the ultrastructural level on the surface membrane and membranes of endoplasmic reticulum and golgi apparatus of human lymphoid cells (Marathe et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…It is also present in various body fluids, such as saliva, serum, bile and urine (Nemesanzky and Lott, 1985;Sener, 1997). GGT has been detected both in blood and bone marrow cells by using cytochemical methods (Szmigielski et al, 1965). It has been demonstrated at the ultrastructural level on the surface membrane and membranes of endoplasmic reticulum and golgi apparatus of human lymphoid cells (Marathe et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…/-Glutamyl transpeptidase has formerly been histochemically demonstrated in mye loid elements of the bone marrow, including mitotic normoblasts and megakaryocytes [7]. The /-glutamyl transpeptidase activity of the marrow lymphocytes was also shown to be significantly lower than that of the lymph node lymphocytes.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, others (Barr and Perry, 1976) have noted negative or weak acid phosphatase activity in normal human peripheral blood T lymphocytes and moderate to strong reactivity in B Received for publication 8 December 1976 and null cells. In addition, other investigators (Szmigielski et al, 1965) have shown that 75% of human peripheral blood lymphocytes and 2-10% of bone marrow lymphocytes contain gamma-glutamyl transpeptidase activity. Since T cells have a similar distribution in the blood and bone marrow, it seemed possible that gamma-glutamyl transpeptidase was also a cytochemical marker for T cells.…”
mentioning
confidence: 94%
“…In addition, other investigators (Szmigielski et al, 1965) have shown that 75% of human peripheral blood lymphocytes and 2-10% of bone marrow lymphocytes contain gamma-glutamyl transpeptidase activity. Since T cells have a similar distribution in the blood and bone marrow, it seemed possible that gamma-glutamyl transpeptidase was also a cytochemical marker for T cells.…”
mentioning
confidence: 94%
See 1 more Smart Citation